Analysis Of Beginning Reading Ability And Difficulties Faced 4th Grade Elementary Students At MI Tarbiyatul Falah - firda amalia aziza (LADU: Journal of Languages and Education, 2023)
Background:  In the form of learning activities in schools, reading is one of the most essential skills that students need to master. The ability to read for students is seen as a determinant of their success in carrying out their learning activities while at school. Purpose: The purpose of this study was to find out how far the beginning reading ability of 4th grade elementary school students at MI Tarbiyatul Falah and the difficulties they face. Design and methods: This study applies a descriptive qualitative method, which is a method that is carried out by visiting data sources directly, then analyzing the data obtained as it is. Researchers collected further data using interview techniques, observation and tests on these students and class teachers to find the causal factors. Results: the researcher draws the conclusion that in students' initial reading skills, each aspect relates to and influences other aspects of reading, and this difficulty is motivated by factors that become obstacles in applying initial reading skills